PENGAWASAN DPRD TERHADAP TINDAK LANJUT HASIL PEMERIKSAAN OLEH BADAN PEMERIKSA KEUANGAN - Muawafah Muawafah; Edi Pranoto (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2022)
The purpose and objective of supervision is to prevent or correct errors, irregularities, non-compliance with the implementation plan and others that are not in accordance with the assigned duties and authorities. So that the results of the implementation of the work are obtained accurately, efficiently and successfully in accordance with the 1 predetermined plan. The supervision carried out by the DPRD on the follow-up to the audit report by the BPK is very important to realize good regional governance, a government free from corruption, collusion and nepotism, as well as evaluation material for the use of regional finance and regional financial reports. recommendations by BPK as a manifestation of the need for improvement in the presentation of reports by regional governments, so that there is an obligation to regional governments to implement recommendations from BPK